IL-2 in the immunotherapy of autoimmunity and cancer - Malek, Thomas (Henry Stewart Talks, 2023)
IL-2Rs, IL-2 and regulatory T cells, Therapy for autoimmune diseases, Low-dose IL-2, Clinical testing, IL-2 for autoimmunity and cancer, Mouse IL-2/CD25 fusion protein, Key properties of IL-2/CD25, IL-2 as a cancer immunotherapy, IL-2-dependent anti-tumor immunity, High-dose IL-2/CD25, Clinical implications